The Relationship Between Increased Neutrophils and the Incidence of Diarrhea in Children at Haji Regional Hospital, Makassar City - Annisa Salsabilah Salam; Abdi Dwiyanto Putra Samosir; Nur Ayu Lestari; Andi Husni Esa; Akhmad Kadir (Journal of Community Health Provision, 2026)
Childhood diarrhea remains a major public health problem in developing countries, including Indonesia, with a prevalence of 10–12% among children under five. Globally, it accounts for approximately 1.7 billion cases and 525,000 deaths annually. Diarrhea is commonly caused by viral infections such as rotavirus, which trigger lymphocyte-dominant immune responses, while bacterial infections such as Escherichia coli and Shigella are associated with neutrophil activation. In tropical regions like Sulawesi, poor hygiene, malnutrition, and seasonal factors further increase the burden of disease. This study aimed to analyze the association between diarrhea and neutrophil elevation in pediatric patients at RSUD Haji Makassar. An analytical observational study with a cross-sectional design was conducted using medical record data of 49 children from July to December 2025. Data were analyzed using univariate and bivariate (chi-square) methods. The results showed that neutrophil elevation occurred in 38.8% of patients, normal levels in 32.7%, and decreased levels in 28.6%. Most patients were male (57.14%) and aged 12–24 months. Statistical analysis revealed no significant association between neutrophil levels and diarrhea incidence (p=0.767). These findings suggest that pediatric diarrhea cases are predominantly influenced by viral infections, which are not associated with neutrophilia, and may also be affected by dehydration and nutritional factors.